Diural fertilizer application affected nitrogen uptake in Vanda via roots and leaves - K. Panjama (2020)
© 2019 International Society for Horticultural Science. All rights reserved. Vanda is an important commercial tropical orchid in Thailand. Orchid growers generally spray fertilizer via both foliar and aerial roots to promote growth and flower quality. The excess fertilizer application is usually done by growers to ensure sufficient fertilizer absorption. However, nutrient uptake and utilization in Vanda is unclear. Therefore this study was conducted to determine the uptake efficiency of Vanda leaves or roots and optimum time of fertilizer application. The 15N tracer (5 mM 15NO3- + 5 mM NH4+) is fed to plant once via leaves or roots with different timing. The experimental designed was 2×4 factorial in CRD, combination of two application methods (via leaves or roots) and four application times (8 am, 12 pm, 4 pm and 8 pm). The results showed that, regardless of diurnal, only foliar fertilizer caused higher 15N uptake with 47.42 µg g-1 DW of concentration in leaves, whereas applied fertilizer via roots obviously gave the higher 15N concentration in stem and roots as 41.40 and 162.38 µg g-1 DW, respectively. For all application times, applied fertilizer via roots resulted in greater amount of 15N content in roots, highly at 12 pm and 4 pm (4.87 and 4.69 mg plant-1, respectively). Thus, it could be suggested that supplying fertilizer via aerial roots of Vanda during 12 pm and 4 pm could stimulate nutrient uptake and accumulation in Vanda.